2020
DOI: 10.3390/ijerph17072248
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Literature Review of E-Cigarette-Related Illness and Injury: Not Just for the Respirologist

Abstract: Following the recent electronic cigarette (e-cigarette) illness outbreak, the current review aimed to collect all related clinical cases for study and analysis and provide a critical synopsis of the proposed injury mechanism. Adhering to PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-analysis) guidelines, e-cigarette-related clinical cases were identified via Google Scholar and PubMed databases. Additionally, references of published case reports and previous review papers were manually searc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
0
20

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(86 citation statements)
references
References 212 publications
1
50
0
20
Order By: Relevance
“…A recent randomized clinical trial of e-cigarettes versus nicotine-replacement therapy showed no serious adverse events related to product use in either group ( 15 ). However, a recent review ( 16 ) described 58 cases of e-cigarette-related respiratory disease, including acute lung injury, organizing pneumonia, eosinophilic pneumonia, and acute respiratory distress syndrome. Among these 58 patients, 1 presented with acute lung injury after switching from conventional cigarettes to e-cigarettes ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent randomized clinical trial of e-cigarettes versus nicotine-replacement therapy showed no serious adverse events related to product use in either group ( 15 ). However, a recent review ( 16 ) described 58 cases of e-cigarette-related respiratory disease, including acute lung injury, organizing pneumonia, eosinophilic pneumonia, and acute respiratory distress syndrome. Among these 58 patients, 1 presented with acute lung injury after switching from conventional cigarettes to e-cigarettes ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…Among these 58 patients, 1 presented with acute lung injury after switching from conventional cigarettes to e-cigarettes ( 17 ). While no single ingredient in e-cigarettes has yet been identified as responsible for respiratory diseases, cannabinoids, nicotine, and the e-liquid constituents are potential causes ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…We performed an advanced search using ‘nicotine’ as the ‘meSH major term’ AND ‘toxicity’ as ‘all field’, with the filters: ‘10 years’ (publication data) and ‘abstract available’ (text availability). In addition, references of all relevant articles, including case reports and retrospective studies, were also evaluated, 8,15,16 as well as those from a prospective observational study of the Oregon Poison Centre, 17 through Google Scholar and CrossRef. We evaluated English and non‐English articles (using Google Translator) including case reports, adults, voluntary ingestion or injection, oral or intravenous intoxication with an e‐liquid.…”
Section: Methodsmentioning
confidence: 99%
“…Poisonings were all caused by the intentional intake of e-liquid, since evidence from the literature about accidental intake was exclusively reported in paediatric cases. 16 Of…”
Section: Re Sultsmentioning
confidence: 99%
“…In first instance, the design of e-cigarettes as electronic nicotine delivery systems has focused the interest of toxicologists on nicotine and on local effects on the respiratory system, but other endpoints of toxicity are also being discussed (Tzortzi et al 2020); current examples are atherosclerosis (Knura et al 2018) and neuroinflammation (Heldt et al 2020). The presence of a considerable number of toxic substances apart from nicotine in the liquid cartridges and in emissions of e-cigarettes has increasingly raised concern (Rehan et al 2018).…”
mentioning
confidence: 99%